Examining the Factors Affecting the Profitability of Commercial Banks - Purna Man Shrestha (MASI Mandiri Edukasi, 2023)
This paper has assessed the determinants of the profitability of commercial banks operating in Nepal. The effect of macroeconomic as well as internal factors on profitability is estimated. For this purpose, ROA is used to measure a bank's profitability. Similarly, liquidity (LIQ), management efficiency (ME), assets quality (AQ), and operational efficiency (OE) are used as internal factors, and consumer price index (CPI), interest rate (IR), and growth rate of broad money supply (M2) are used as macro-economic factors. Based on the result of panel data analysis, this paper revealed that bank-specific and macroeconomic factors play an essential role in determining profitability. Further, this paper found that LIQ, ME, AQ, CPI, and IR substantially influence the profitability of banks operating in Nepal. Thus, this paper concluded that the bank management should improve its liquidity, efficiency of management, and quality of assets to improve profitability. Likewise, the bank management can benefit from increasing CPI and IR to improve profitability.